METODE PENELITIAN KEBIJAKAN - Murjani Murjani (Cross-border, 2022)
Policy research is also often done by analyzing existing documents. Documents can be obtained from research institutions or research reports. If the data is sourced from documents, the appropriate research method used is document analysis, whereas if the data is sourced from existing research reports, the method used is meta-analysis.